Recent challenges in the social regulation of new emerging technologies - Mali, Franc (Teorija in praksa, 2014)
Synthetic biology represents one of the most promising areas of progress in the new emerging technologies. It is a transdisciplinary area of research that combines molecular biology, engineering, biochemistry, computer sciences and other disciplines in new practices of biological design that are diverse in their approaches and full of hope in their promises. In the article, synthetic biology is presented as a good case for understanding the wider ethical, legal and social aspects of recent progress in the new emerging sciences and technologies. More specifically, the precarious issues of risk, commodification and legal protection, which are the central points of discussion in the article, are emerging as salient points not only in this technological "niche", but in practically all modern technologies.
Keywords: Ethics; Etika; Intelektualna lastnina; Intellectual property; New technologies; Nove tehnologije; sintezna biologija; Sociologija znanosti; Sociology of science